Neglected subluxation of the hip after trauma: A case report. (September 2020) - Matsubayashi, Shohei; Kanzaki, Eri; Tsujimoto, Ritsu; Osaki, Makoto; Wada, Akifusa
Abstract: Introduction: In children, the pelvis contains a large amount of cartilage components; therefore, when traumatic hip dislocation spontaneously reduces, it can be impossible to see on X-ray or computed tomography (CT) images in some cases, which can delay its detection. Case presentation: We report the case of a 10-year-old boy who was injured by being hit by a car while walking. Upon diagnosis of pelvic ring fracture, the patient received conservative treatment. Seven months after injury, the patient was referred to our department with the chief complaint of limping. Diagnosis: Marked limitation was observed in the left hip with extension of −40°, abduction of 10°, and internal rotation of 20°. X-ray revealed narrowing of the left hip joint space, with deformity of the femoral head, obturator foramen narrowing, and the break in the Shenton line. CT revealed proximal dislocation of the posterior acetabular wall and posterior subluxation of the femoral head. Magnetic resonance imaging (MRI) revealed necrosis of the femoral head. Intervention: Operation was performed with soft tissue dissection, varus-extension-internal rotation femoral osteotomy, greater trochanteric epiphysiodesis, and pelvic osteotomy (incomplete periacetabular osteotomy: IPO). After operation, complete paralysis of the sciatic nerve was observed. Outcomes: At 1 year after operation, the patient's limited range of motion (ROM) and femoral head necrosis had improved. The sciatic nerve paralysis had fully recovered. Conclusion: If hip extension, abduction, and internal rotation are limited and X-ray reveals a break in the Shenton line., subluxation of the hip should be suspected. Highlights: Pelvic fractures in children. Limited ROM in hip. Break in Shenton line. Subluxation of hip.